(untitled) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2022)
This article aims to determines the protectorate position as dependency of the British empire. The protectorate issues being debated among scholars for certifying the Malay States position during the British colonial period. By literally interpretation of protectorate term "protectorate" some parties claimed that the Malay States was never been colonised. However, what is the concept or real system of the protectorate from the British colonial perspective? The study used history methodology by collecting primary sources from the National Archives of Malaysia, the National Archives of United Kingdom and the National University of Malaysia’s Library. The Colonial Office’s documents in series CO 717, CO 273, CO 576 and FCO 141, which between 1920s and 1930s were the main sources used to answer the stated research question. By using the sources, this article formulates the exact position of the protectorate and the Malay States in the British empire. The study finds that, as protectorates, the Malay States were the dependencies in the British empire. Nevertheless, the British jurisdiction limited as stipulated in the agreement with the Malay Rulers’. The British only recognised the Malay Rulers sovereignty of immune from jurisdiction of the courts, while the administrative and legislative sovereign under the British government jurisdiction through the Colonial Office. Although the imperial laws do not apply directly in the Malay States, the British used the legislative council to endorsed its implementation.